2017
DOI: 10.1051/epjconf/201715703018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Li conditioning on Lower Hybrid Current Drive efficiency in H-mode and L- mode plasmas on EAST

Abstract: Abstract. The lower hybrid current drive efficiency on the EAST tokamak is estimated on a large database of low loop voltage discharges (V L <120mV) covering the 2016 campaign starting with lithium-free plasma facing components and ending with strong cumulated deposition of lithium. The efficiency is found to vary in a wide range from 0.6 to 1.2×10 19 A.W -1 .m -2 . No deleterious effect of the density on the efficiency is found between 2.3 and 3.2×10 19 m -3 . The high efficiency occurs after strong lithium e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The results indicate that LHCD efficiency is enhanced with strong lithium wall conditioning, according to the comparison between different lithium coating levels. Good wall conditioning can reduce edge recycling, thus can increase the critical density for anomalous loss of CD efficiency [37]. This is consistent with PI modelling results [38] showing that strong lithiation can reduce the PI intensity, due to the higher temperature at the plasma edge with the strong lithiation.…”
Section: Lhcd Efficiency At Higher Densitysupporting
confidence: 85%
“…The results indicate that LHCD efficiency is enhanced with strong lithium wall conditioning, according to the comparison between different lithium coating levels. Good wall conditioning can reduce edge recycling, thus can increase the critical density for anomalous loss of CD efficiency [37]. This is consistent with PI modelling results [38] showing that strong lithiation can reduce the PI intensity, due to the higher temperature at the plasma edge with the strong lithiation.…”
Section: Lhcd Efficiency At Higher Densitysupporting
confidence: 85%
“…The simulated results are summarized in table 2. It is found that the predicted CD efficiency of the FAM can match with the experiment when an empirical diffusion coefficient of the fast electrons D st = 1 m 2 s −1 is included in the calculation according to [48,49]. The LH current driven by the PAM alone with 1.6 MW power is predicted to be ∼154 kA, corresponding to a CD efficiency ∼0.66 × 10 19 AW −1 m −2 , which is very close to that estimated by the N || -weighted directivity (∼0.61 × 10 19 AW −1 m −2 ).…”
Section: Summary and Discussionmentioning
confidence: 83%
“…It is hypothesized that these four discharges in figure 2 have experienced a high level of parasitic SOL losses, perhaps due to inefficient wall conditioning. Wall conditioning is known to improve current drive efficiency on EAST [42,51,52]. This speculation is supported by a recent LHCD experiment under lithiation [53]: a near non-inductive 500 kA discharge is sustained by 1.5 MW, rather than ∼3 MW, of the 4.6 GHz power at the line-averaged density of 2 × 10 19 m −3 .…”
Section: Ray-tracing/fokker-planck Code: Genray/cql3dmentioning
confidence: 91%